ANALYSIS OF IMMUNOGYSTOCHEMICAL EXAMINATION OF RESPIRATORY ORGANS IN EXPERIMENTAL BRONCHOECTASIS - Khamidova Farida Muinovna; Zhovliyeva Mavlyuda Baxtiyor qizi; Urakov Kuvandik Nematovich (Scholar Express Journals, 2024)
Immunohistochemical methods for the study of lung tissue in bronchiectatic disease in experimental animal conditions are necessary for a deeper understanding of the cellular and molecular mechanisms of chronic respiratory diseases and the development of new approaches to their diagnosis and therapy
Keywords: bronchi; lungs; chronic inflammation